I want to understand something about the derivation of $\text{Var}(X) = E[X^2] - (E[X])^2$

Variance is defined as the expected squared difference between a random variable and the mean (expected value): $\text{Var}(X) = E[(X - \mu)^2]$


$\operatorname{Var}(X) = E[(X - \mu)^2]$

$\operatorname{Var}(X) = E[(X - E[X])^2]$

$\operatorname{Var}(X) = E[(X - E[X])(X - E[X])]$

$\operatorname{Var}(X) = E[X^2 - 2XE[X] + (E[X])^2]$

$\operatorname{Var}(X) = E[X^2] - 2E[XE[X]] + E[(E[X])^2]$

$\operatorname{Var}(X) = E[X^2] - 2E[E[X]E[X]] + E[(E[X])^2]$

$\operatorname{Var}(X) = E[X^2] - 2(E[X])^2 + (E[X])^2$

$\operatorname{Var}(X) = E[X^2] - (E[X])^2$

What I don't quite understand is the steps that get us from $E[XE[X]]$ to $E[E[X]E[X]]$ to $(E[X])^2$, also $E[(E[X])^2]$ to $(E[X])^2$.

While I'm sure these jumps are intuitive and obvious I would still like to understand how we can (more formally) make these jumps / consider them mathematically equivalent.

  • 1
    $\begingroup$ E[c] = c when c is a constant. E[X] is a constant itself, so E[E[X]] = E[X]. $\endgroup$ – o0BlueBeast0o Jul 18 '16 at 20:37
  • 1
    $\begingroup$ I prefer to think of it as $E[X~E[X]] = E[X]\cdot E[X]$. The expectation operator $E[~]$ is linear, so $E[X+Y] = E[X]+E[Y]$. Also, $E[\alpha X] = \alpha E[X]$ for constant $\alpha$. As $E[X]$ is a constant, the constant can be pulled out of $E[X~E[X]]$ $\endgroup$ – JMoravitz Jul 18 '16 at 20:39
  • $\begingroup$ Isn't anything a constant assuming we know the answer on the righthand side of an equation? $\endgroup$ – user6596353 Jul 18 '16 at 20:42
  • $\begingroup$ And how can we prove that $E[c] = c$ for constant $c$? $\endgroup$ – user6596353 Jul 18 '16 at 20:43
  • 1
    $\begingroup$ If the random variable $W$ is the amount you get from one play of a gambling game, then $E(W)$ is the average amount you get. If $W$ is constant, say $c$, then every time you get $c$, so on average you get $c$. $\endgroup$ – André Nicolas Jul 18 '16 at 20:55

$\newcommand{\E}{\operatorname{E}}$It should not have been written as $$ \E[X\E[X]] = \E[\E[X]\E[X]]. $$ Instead, it should have said $$ \E[X\E[X]] = \E[X] \E[X]. $$ The justification is this: $$ \E[X\cdot5] = 5\E[X], $$ and similarly for any other constant besides $5$. And in this context, "constant" means "not random". So just treat $\E[X]$ the same way you treat $5$, because it's a constant.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.